Pengaruh Struktur Organisasi dan Pengawasan Terhadap Kepuasan Kerja Kepala Sekolah Pada SMA Swasta di Kabupaten Bogor: Manajemen Pendidikan - Subaiki Ikhwan (Al Ashriyyah, 2015)
This study aims to determine the influence of organizational structure and controlling to job satisfaction in Senior High School of District Bogor. This research uses causal path analysis. Technique of data collecting is using the instrument form questionnaire. This instrument is calibrated with the test item, validity and reliability coefficients. The number of 62 head master‟s as sample was selected by proportional random sampling. The result of this research indicated that, 1) There is a direct influence of organizational structure toward the job satisfaction, 2) There is a direct influence of controlling toward the job satisfaction, 3) There is a direct influence of organizational structure toward the controling.